PENGARUH PENGEMBANGAN KARIR, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR UNIT PENYELENGGARA PELABUHAN WEDA - Talib, Hardi (Cahaya Ilmu Bangsa, 2025)
The success of government organizations really depends on the performance of their employees, especially Civil Servants (PNS). In North Maluku Province, the career development of employees in the Port Management Unit is not yet optimal, with some employees working outside their competence. This indicates the need for career development based on employee abilities, competencies and needs. This research aims to analyze the influence of career development, work motivation and discipline on employee performance at the North Maluku Province Port Administration Unit Office. A survey approach was used with a questionnaire as a data collection tool. There were 103 participants, all staff at the Port Administration Unit Office. Data were analyzed using multiple linear regression after classical assumption testing. The research results show that career development and work motivation have a significant effect on employee performance, while work discipline has a smaller effect. Elements related to professional growth and inspiration in the workplace increase employee productivity. This research suggests the importance of career development in accordance with competencies to improve performance, as well as managing motivation and discipline in the workplace to increase employee productivity.